Sustainability: A case study of a Malaysian public university - Sangaralingam, Jayaeswari; Md Isa, Filzah (2012)
This paper briefly introduces the scene of tertiary education around the world and in Malaysia particularly.An analysis was carried on a public university in Malaysia and the findings focused on a major issue: cost containment and sustainability.The paper discusses the issue and provides recommendation on how the university is able to be sustainable in the following areas: traveling and subsistence; communication and utilities; and consumable.